Integrated universal soil loss equation (USLE) and Geographical Information System (GIS) for soil erosion estimation in A Sap basin: Central Vietnam - Pham, Tung Gia; Degener, Jan; Kappas, Martin (International Soil and Water Conservation Research, 2018)
Central Vietnam is very susceptible to soil erosion due to its complicated terrain and heavy rainfall. The objective of this study was to quantify soil erosion in the A Sap river basin, A Luoi district, Thua Thien Hue Province, Vietnam, using the Universal Soil Loss Equation (USLE) and Geographical Information System (GIS). The results showed that 34% of land area lost accumulated to 10tha−1year−1 while 47% of the total area lost less than 1tha−1year−1. Natural forest land lost the most with an average of about 19tha−1year−1, followed by plantation forest with approximately 7tha−1year−1 and other agricultural lands at 3.70 and 1.45tha−1year−1 for yearly crops and paddy rice, respectively. Soil erosion was most sensitive to the topographic factor (LS), followed by the practice support factor (P), soil erodibility factor (K), cropping management (C), and the rainfall erosivity factor (R). Implications are that changes to the cultivated calendar and implementing intercropping are effective ways to prevent soil erosion in cultivated lands. Furthermore, introducing broad leaves trees for mountainous areas in A Sap basin was the most effective practice in reducing soil erosion. The study also pointed out that the combination of available data sources used with the USLE and GIS technology is a viable option to calculate soil erosion in Central Vietnam, which would allow targeted attention toward a solution is to reduce future soil erosion.